Estresse ocupacional em gestores: estudo nas secretarias de estado de Minas Gerais - Lyovan Neves Maffia (2013)
The research that led to this master thesis can be classified as a descriptive study, with quantitative and qualitative approach. The aim of this study was to identify and analyze frames of occupational stress, its causes, major symptoms, regulatory mechanisms and impact indicators on the productivity of workers occupying the position of managers. We analyzed 181 managers from Secretaries of State of Minas Gerais. The questionnaire adherent to the Theoretical Model to Explain Managers Occupational Stress developed by Zille (2005), was adapted for this study and used as an instrument for data collection. The softwares Excel and SPSS Statistical Package for the Social Sciences were used for data analysis. Were also conducted semistructured interviews with 12 managers, that were analyzed through the content analysis. The results showed that 26.0% of the managers in the sample showed no sign of occupational stress, 26.0% presented light to moderate stress level, 43% intense stress conditions and 5% had very intense stress conditions. The main symptoms of stress detected were: fatigue, pain in the muscles of the neck and shoulders, anxiety, nervousness and irritability. The main sources of excessive tension existing in the work environment were: execution of multiple activities at the same time and with a high degree of levy; many deadlines do manage and tight deadlines, the requirement of high production with few resources, the execution of complex work and, finally, work philosophy guided by obsession and compulsion for results. The main sources of tension identified acting at the individual were: thinking and/or performing two or more tasks at the same time, even when there is no requirement to do so, with difficulty in completing them; having the day filled with a series of commitments, with little or no free time; living in a hurry, performing increasingly more tasks, within the same time lapse; and not being able to take off the job from the mind. Were also analyzed the sources of tension specific of the manager's work, noted as key: having no time to live with a better quality of life; experiencing conflicts arising from the need to be innovative, show autonomy and be subjected to the rules of the institution, all at the same time; having difficulty reconciling professional with personal life; and experiencing conflict by perceiving that they are overloaded, but are not able to question the situation as they are exercising management functions. The regulatory mechanisms used by most state public managers to face the tensioning situations were: personal experience in solving problems at work; the possibility to rest on a regular basis; taking time to rest and relax during weekends and holidays; cooperation among peers; and the possibility of enjoying vacations regularly. Indicators of stress impact on the productivity of the managers that were pointed out more frequently, were: having difficulty in remembering recent events related to work, that previously were easily remembered; desire to leave this job to find a better one; having difficulty in concentrating on the job; and having the feeling of demotivation with the job. In this study it was verified that widowed managers had lower stress levels when compared to singles, married or other marital bond. In relation to the habit of smoking, it was found that smokers had higher levels of stress when compared to nonsmokers. In the other hand, the frequent practitioners of physical activity had lower levels of stress than non-practitioners. There was also an association between variables: smoking, alcohol consumption and physical activity with occupational stress.